Study on Shift Work Problems Among Security Team at University Tun Hussein Onn Malaysia, Parit Raja - MOHAMAD ZAMRI, MUHAMAD ADHAM ZUHRI; ISMAIL, SHAFAWI (Progress in Engineering Application and Technology, 2023)
Shift work, particularly that including night work has causes many health problems among workers in Malaysia. The aims of these study are to identify health problems and issues related to shift works and come out with new intervention plans to reduce the impacts to the shift workers. Data were analysed using SPSS software to get descriptive statistics on the demographic parameters of the respondents and to investigate the link between six factors affecting shift workers. The ANOVA findings revealed a statistically significant difference at p0.05, n= 50, p